Outcomes of Consistent Conservative Management for Acute Cholecystitis Followed by Delayed Cholecystectomy. Issue 5 (October 2017) - Komatsu, Shohei; Tsuchida, Shinobu; Wakahara, Tomoyuki; Ueno, Nozomi; Toyokawa, Akihiro; Watanabe, Akihiko; Sugahara, Atsushi; Mukai, Hidekazu
Abstract : Objective: This study's objective was to assess outcomes of a totally conservative strategy for acute cholecystitis (AC) followed by delayed elective cholecystectomy. Patients and Methods: Consecutive patients who underwent cholecystectomy for AC were divided into the Emergent and Elective cholecystectomy groups. Patients in the elective cholecystectomy group were divided into early, medium, and late groups according to time from symptoms onset. Results: The success rate for conservative management reached 97.2%. Increased blood loss and a higher conversion rate were significantly associated with the emergent group. Patients in the late group had significantly lower operative time and tended to have lower blood loss and less frequent conversion to open surgery than those in the early and medium groups. Conclusions: Most AC cases could be managed conservatively, and elective cholecystectomy was performed safely regardless of the time. Elective cholecystectomy carried out in late phase was likely to be associated with decreased surgical difficulty.